What was the impact of COVID-19 restrictions on unintentional injuries, in Canada and globally? A scoping review investigating how lockdown measures impacted the global burden of unintentional injury - Karmali, Shazya; Saxena, Shikha; Richards, Olivia; Thompson, Wendy; McFaull, Steven R.; Pike, Ian (Frontiers in Public Health, 2024)
Background: Injuries are among the leading causes for hospitalizations and emergency department (ED) visits. COVID-19 restrictions ensured safety to Canadians, but also negatively impacted health outcomes, including increasing rates of certain injuries. These differences in trends have been reported internationally however the evidence is scattered and needs to be better understood to identify opportunities for public education and to prepare for future outbreaks. Objective: A scoping review was conducted to synthesize evidence regarding the impact of COVID-19 restrictions on unintentional injuries in Canada, compared to other countries. Methods: Studies investigating unintentional injuries among all ages during COVID-19 from any country, published in English between December 2019 and July 2021, were included. Intentional injuries and/or previous pandemics were excluded. Four databases were searched (MEDLINE, Embase, Web of Science, SPORTDiscus), and a grey literature search was also conducted. Results: The search yielded 3,041 results, and 189 articles were selected for extraction. A total of 41 reports were included from the grey literature search. Final studies included research from: Europe (n = 85); North America (n = 44); Asia (n = 32); Oceania (n = 12); Africa (n = 8); South America (n = 4); and multi-country (n = 4). Most studies reported higher occurrence of injuries/trauma among males, and the average age across studies was 46 years. The following mechanisms of injury were reported on most frequently: motor vehicle collisions (MVCs; n = 134), falls (n = 104), sports/recreation (n = 65), non-motorized vehicle (n = 31), and occupational (n = 24). Injuries occurring at home (e.g., gardening, home improvement projects) increased, and injuries occurring at schools, workplaces, and public spaces decreased. Overall, decreases were observed in occupational injuries and those resulting from sport/recreation, pedestrian-related, and crush/trap incidents. Decreases were also seen in MVCs and burns, however the severity of injury from these causes increased during the pandemic period. Increases were observed in poisonings, non-motorized vehicle collisions, lacerations, drownings, trampoline injuries; and, foreign body ingestions. Implications: Findings from this review can inform interventions and policies to identify gaps in public education, promote safety within the home, and decrease the